Application of the science model community-based problem solving technology in improving learning outcomes, science process skills, and students scientific attitudes - Meganita Meganita; Pamella Mercy Papilaya; Dominggus Rumahlatu (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2022)
The STS (science technology and society) learning model teaches students to pay attention to problems that then emerge as other impacts of the use of new technologies in social life. Whereas the Problem Solving learning model teaches students to be trained in problem-solving using creative ways. The purpose of this study was to analyze the effect of the application of STS based problem-solving learning models on the learning outcomes, science process skills, scientific attitude of senior high school 6 Ambon. The research was conducted from January to February 2020. The research design was a quasi-experimental study using a non-equivalent group design. Data were analyzed using descriptive and inferential statistics using the ANCOVA and ANOVA tests. Descriptive statistics are used to explain the range of research data on cognitive learning outcomes, science process skills, and scientific attitudes in the table. ANCOVA test is used to analyze the effect of learning models on cognitive learning outcomes. ANOVA test is used to analyze the effect of learning models on scientific process skills and scientific attitudes. The results showed that the distribution of cognitive learning outcomes, science process skills, and scientific attitudes of students in the experimental class taught using STS based problem solving learning models were better than students taught using conventional learning models (STAD). ANCOVA statistical test shows that the significant value is 0,000 <0.05. This shows that the learning model influences students' cognitive learning outcomes. ANOVA statistical test showed that the significant value was 0,000 <0.05. This shows that the learning model influences the science process skills and scientific attitude. The stages in the STS based problem solving learning models can accommodate cognitive learning outcomes, process skills, and scientific attitudes of senior high school 6 Ambon on Environmental Friendly Technology material.